Does social capital matter in corporate decisions? Evidence from corporate tax avoidance - Iftekhar Hasan; Chun-Keung (Stan) Hoi; Qiang Wu; Hao Zhang (Bank of Finland, 2017)
We investigate whether the levels of social capital in US counties, as captured by strength of civic norms and density of social networks in the counties, are systematically related to tax avoidance activities of corporations with headquarters located in the counties. We find strong negative associations between social capital and corporate tax avoidance, as captured by effective tax rates and book-tax differences. These results are incremental to the effects of local religiosity and firm culture toward socially-irresponsible activities. They are robust to using organ donation as an alternative social capital proxy and fixed effect regressions. They extend to aggressive tax avoidance practices. Additionally, we provide corroborating evidence using firms with headquarter relocation that changes the exposure to social capital. We conclude that social capital surrounding corporate headquarters provides environmental influences constraining corporate tax avoidance.
URN:NBN:fi:bof-201708111505
Keywords: A13; H26; M40; M41; Z13; 330